Acceptance of the Raileo Application and Its Impact on Employee Performance at PT Kereta Api Indonesia (Persero) DAOP III - Reza Faizal Anshori; Najmudin Najmudin; Sudarto Sudarto (Citakonsultindo, 2024)
This online presence not only makes it easier to record attendance but also eases the work of employees in creating monthly attendance reports. Employees value the ease and efficiency of using the presence system, which supports the effectiveness of work in an agency. However, the implementation of KAI Mobile Presence, which came into effect in October 2019 and was developed into RAILEO in October 2020, is still not optimal. Therefore, research is needed to ensure that all employees of PT. KAI (Persero) Daop III can accept and implement RAILEO as well as possible. This study aims to analyze the factors influencing the acceptance of the RAILEO application and its impact on the performance of PT. Kereta Api Indonesia (Persero) Daop III. The research seeks to improve worker performance at PT. Kereta Api Indonesia (Persero) Daop III. Conducted at PT. Kereta Api Indonesia (Persero) Daop III, the results of this study are: (1) perceived usefulness affects the acceptance of the RAILEO application, (2) ease of use affects the acceptance of the RAILEO application, (3) security and privacy affect the acceptance of the RAILEO application, (4) the quality of the internet network affects the acceptance of the RAILEO application, (5) acceptance of the RAILEO application affects performance, and (6) perceived enjoyment has no effect on the acceptance of the RAILEO application.